PELAKSANAAN MAKSIM KUALITAS DAN KUANTITAS DALAM IKLAN KOMERSIAL DI TELEVISI (KAJIAN ANALISIS PERCAKAPAN) - Redo Andi Marta (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2020)
This study aims to explain the implementation of the maxim of quality and quantity in a conversation. Conversation can be done under any circumstances. In this study the conversations were scrutinized conversations in a commercial commercial on television. This type of research is a research based on qualitative approach using descriptive method. Source of date used speech-speech in the form of conversations that exist in commercial commercials on television. The date in this research is conversation speech which contains the maxim of quality and quantity. The results of this commercial advertisement in the form of five types of commercial advertising include Yamaha Yupiter MX version of "Valentino Rosi", Pepsodent "candidate-in-law" version, ABC soy sauce version, US Card "King dangdut" version, and soapy Lifebouy Soap version. Recapitulation of research data found contained maximization of quantity in the form of 4 date and fulfillment maxim quality 3 date. Meanwhile, the maximal violation of quantity amounted to 3 date and violation of quality invoked amounted to 4 date.